2020
DOI: 10.1298/ptr.e10023
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous application of carbon dioxide improves contractures after immobilization of rat knee joint

Abstract: Joint contractures are a major complication following joint immobilization. However, no fully effective treatment has yet been found. Recently, carbon dioxide (CO2) therapy was developed and verified this therapeutic application in various disorders. We aimed to verify the efficacy of transcutaneous CO2 therapy for immobilization-induced joint contracture. Method: Twenty-two Wistar rats were randomly assigned to three groups: caged control, those untreated after joint immobilization, and those treated after jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In the CO 2 group, TGF‐β expression was lower than that in the control group during the second half of the experiment, suggesting that this may have led to reduced scarring. In a previous study, CO 2 therapy was shown to reduce TGF‐β1 protein levels in joint capsules associated with fibrosis and improve the passive range of motion in a rat model 28 . Here, the CO 2 paste significantly prevented fibrosis during muscle regeneration, which was likely due to the early downregulation of TGF‐β, a major trigger of the fibrosis cascade.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In the CO 2 group, TGF‐β expression was lower than that in the control group during the second half of the experiment, suggesting that this may have led to reduced scarring. In a previous study, CO 2 therapy was shown to reduce TGF‐β1 protein levels in joint capsules associated with fibrosis and improve the passive range of motion in a rat model 28 . Here, the CO 2 paste significantly prevented fibrosis during muscle regeneration, which was likely due to the early downregulation of TGF‐β, a major trigger of the fibrosis cascade.…”
Section: Discussionmentioning
confidence: 63%
“…In a previous study, CO 2 therapy was shown to reduce TGF‐β1 protein levels in joint capsules associated with fibrosis and improve the passive range of motion in a rat model. 28 Here, the CO 2 paste significantly prevented fibrosis during muscle regeneration, which was likely due to the early downregulation of TGF‐β, a major trigger of the fibrosis cascade. In addition, fibrin induces the expression of inflammatory chemokines and cytokines that promote muscle degeneration, such as IL‐6 and IL‐1β.…”
Section: Discussionmentioning
confidence: 81%
“…We have developed a new transcutaneous CO 2 application system using 100% CO 2 gas and a transdermal CO 2 absorption-enhancing hydrogel [16]. This treatment has been used previously in several animal models, and it can increase local blood flow, prevent muscle atrophy and contraction, and recover muscle damage [18][19][20][21][22][23]. Oe et al demonstrated similar changes to those that occur within muscles when aerobic exercise is performed [23].…”
Section: Plos Onementioning
confidence: 99%
“…Carbon dioxide (CO 2 ) therapy is widely known as an effective treatment to improve blood flow and has been indicated for various diseases such as heart disease and skin conditions [16]. We demonstrated that transcutaneous application of CO 2 could improve local blood flow and promote the suppression of muscle atrophy and contraction, as well as the recovery of muscle damage [17][18][19][20][21][22][23]. However, while we have demonstrated the effect of transcutaneous application of CO 2 in suppressing tumor growth [24], we have not demonstrated the effect of cancer cachexia.…”
Section: Introductionmentioning
confidence: 99%